VOLATILE ORGANIC COMPOUNDS IN MOTOR VEHICLE INTERIORS UNDER VARIOUS CONDITIONS AND THEIR EFFECT ON HUMAN HEALTH - Jan VERNER; Marie SEJKOROVÁ; Petr VESELÍK (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of this paper is to estimate the mass concentrations of volatile organic compounds (VOCs) such as benzene (B), toluene (T), ethylbenzene (E) and m-, p-, o-xylenes (X) inside of the driver-compartment of motor vehicles. The results were compared with the Czech limits for indoor environments and the external concentrations. The experiments were carried out on various routes with different methods of ventilation. The volatile emissions detected inside the vehicle were investigated in the city of Brno, Czech Republic. Cabin air was collected using desorption tubes and the samples were analysed by thermal desorption gas chromatography with a flame ionisation detector coupled with a mass detector. VOC concentrations detected in the cabin of the vehicle ranged from 2.93 µg.m-3 to 7.96 µg.m-3 for benzene, 1.42 µg.m-3 to 4.38 µg.m-3. for toluene, 44.06 µg.m-3 to 152.00 µg.m-3 for ethylbenzene and 63.07 µg.m-3 to 479.62 µg.m-3 for xylenes. The indoor limit value for benzene, according to the Czech standard, is 7 µg.m-3. Levels of toluene were consistently below the Czech hourly standard, whose value according to the Czech standard is 300 µg.m-3. According to our findings, various methods of ventilation are an important factor influencing the BTEX pollution levels within the interior of the vehicle. In addition, this paper presents the influence results of benzene on the health of passengers inside the cabin of the vehicle. The results show that all age categories, especially children under the age of two, are exposed to increased health risks.